Evaluation of Trichoderma asperellum B1902 in controlling Fusarium wilt of cavendish banana cultivar - Syd Abdul Rahman, Sharifah Siti Maryam; Mohd Zainudin, Nur Ain Izzati; Abd. Aziz, Nor Azwady (Penerbit Universiti Kebangsaan Malaysia, 2021)
Trichoderma species is one of the microorganisms with antagonistic properties as biological control agents. In the banana industry, Fusarium wilt disease caused by Fusarium oxysporum f. sp. cubense (Foc) has been practically managed using chemical pesticides that led to environmental disruptions, ineffective conditions and disease resistance. In preliminary study, T. asperellum gave better result compared to other species in inhibiting the growth of Foc in in vitro condition. Therefore, the aim of this study was to examine the effects of T. asperellum as a biological control of Fusarium wilt disease of banana. A total of 326 fungal isolates were isolated from soil samples obtained around Malaysia and identified as Trichoderma species based on phenotype characteristics. The species identity for the best candidates from dual culture test was confirmed based on internal transcribed spacers (ITS) and translation elongation factor 1 alpha (TEF-1α) sequence identity. In dual culture test, findings showed that three isolates with a high percentage inhibition of radial growth (PIRG) were observed in plates of T. asperellum isolates B1902 (84.85%), T2007 (77.78%) and C1667 (75.76%), which successfully inhibited the growth of F. oxysporum f. sp. cubense isolate 9888. Based on in vivo test, the best candidate was T. asperellum B1902 with lower disease severity index (DSI) value of 0.2 compared to the inoculated control with DSI of 3.6. As a conclusion, T. asperellum B1902 can be used as an alternative treatment in managing Fusarium wilt disease. Hence, future study should be focused on applying T. asperellum as a biocontrol agent in the field and controlling other plant diseases in the agricultural plantation.